Culture of the cherry - Holsinger, Clarence V. (My University, 1895)
Introduction: To those who are contemplating the vocation of horticulture, the question arises, Will it pay to be a specialist in this state? This thought is probably inspired largely by the fact, that we have few cities with population sufficient to consume the product of a large orchard. But now with the present means of transportation, there is no reason why the surplus cannot be shipped to some more distant markets. With the apple, it has already been demonstrated that it is a paying crop; and while other fruits have not been tried to any great extent, save in one or two cases, they have been a financial success. In this western country thus far the cherry has not been grown very extensively; though at present it is in high favor with the fruit growers in the eastern part of the state, many of whom are planting out large orchards.
Citation: Holsinger, Clarence V. Culture of the cherry. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Cherry orchards; Horticulture; Cherry; Theses; Manuscripts (documents)